Improvement of egg internal quality of local ducks through star gooseberry leaf meal inclusion in ration - Anggraeni, Anggraeni; Sudrajat, Deden; Handarini, Ristika; Malik, Burhanudin (Journal of Advanced Veterinary and Animal Research, 2023)
Objectives: The use of dried star gooseberry leaf extract (DSGLE) in rations and its effects on the egg internal quality of local ducks were examined. Materials and Methods: A total of 100 9-month-old local ducks weighing 1,406.25 ± 211.32 gm were randomly allocated into 5 treatments and 5 replicates in a completely randomized design. The birds were reared in 25 battery cages (4 birds each) and fed rations containing 0, 0.5%, 1.0%, 1.5%, and 2.0% DSGLE. Results: Eggs of ducks fed DSGLE had significantly lower saturated fatty acid (SFA) (30.66%– 32.53%) than those of control ducks (36.23%). Egg polyunsaturated fatty acids (PUFA) increased from 2.29% (control) to 2.61% (2.0% DSGLE) and 2.76% (1.5% DSGLE), while egg monounsaturated fatty acid (MUFA) contents were not significantly different. The fatty acids of the whole edible part of eggs (albumen + yolk) were composed mainly of MUFA (40.19%–44.34%), followed by SFA (30.66%–36.22%), and PUFA (2.29%–2.76%). Malondialdehyde contents were reduced from 6.07 to 4.92 µg/gm (19%) in egg yolk and from 1.50 to 0.62 µg/gm (59%) in egg white, and thiobarbituric acid reactive substances values of the eggs were reduced from 0.93 to 1.65 (77%). The egg cholesterol level of ducks fed 2% DSGLE (21.94 mg/gm) was about 28.5% lower than that of eggs from control ducks (30.67 mg/gm) of eggs of control ducks. The egg white and egg yolk protein contents (12.31% and 16.35%) of treated ducks were lower than those in the control group (13.58% and 17.47%). Conclusion: The inclusion of SGLE in rations could be used to produce healthy duck eggs with no oxidative damage. J. Adv. Vet. Anim. Res., 10(2): 421–428, September 2023 http://doi.org/10.5455/javar.2023.j695